Motif Berperilaku Kepala Desa Pada Penyelenggaraan Pemerintahan Desa di Kabupaten Minahasa Selatan - Goni, Shirley Y, V, I; Londa, Very Y (JURNAL ILMIAH SOCIETY, 2014)
The behavior of the village chief is expected to build the image quality public services, but in reality the implementation of public services have not been able to walk properly due to the unavailability of the service personnel are professional, dedicated, accountable and responsive and loyal to his duties as civil servants and public servants. By using a qualitative approach was found that social status (achievement, prestige / status position and power / power, and needs (income and appreciation) are two underlying motives in the village head behaves In Governance in South Minahasa Regency Village. Loyalty and professional as media which can bridge the social status and the need to make quality services. Keywords: Motive behavior, social status, Supplies, Services